Indigenous and improved adaptation technologies in response to climate change adaptation and barriers among smallholder farmers in the East Wollega Zone of Oromia, Ethiopia - Teka Bekuma; Girma Mamo; Alemayehu Regassa (Research in Globalization, 2023)
Agriculture is the foundation of economy for Ethiopia. The majority of people in the study area rely on rain-fed subsistence agriculture for their livelihood. As a result, smallholder farmers were more susceptible to climate change due to their reliance on a single rain season and lack of climate change adaptation technologies. The sustainability of food crop production, which employs the majority of the labor force in the nation, is threatened by climate change. The study's objectives were to look at indigenous and improved adaptation technologies in reaction to local climate change effects and barriers to adaptation among smallholder farmers. A closed-ended, semi-structured questionnaire was used to gather the data from 400 smallholder farmer household heads. An analysis of the variables influencing farmers' decisions regarding climate change adaptation was conducted using binary logistic regression model. The fitness and accuracy of the model were examined using an omnibus test of model coefficients. The study's findings showed that absence of crop insurance, a lack of training and demonstration, a lack of non-farm employment, a lack of weather forecasting and early warning, shortage of finance, the high price of farm inputs, and reliance on a single rain season were the main barriers preventing farmers from adapting to climate change. The most popular indigenous adaptation techniques used by smallholder farmers included mixed cropping of local variety, reducing social and religious rituals, mixed farming (local crop and livestock), and reducing the amount of food consumed. The primary improved adaptation strategies used by the farmers included the use of chemical fertilizers, various agrochemicals, and soil and water conservation methods. The binary logistic regression model's findings showed that access to extension services by household heads significantly and favorably influenced farmers' decisions to scale back social and religious rituals, reduce food consumption, sell livestock, and adopt improved mixed farming as a means of adapting to climate change. Farm experience significantly influenced the farmers' decision to practice improved mixed farming; access to the market significantly affected farmers' decision on soil and water conservation practices; and the age of the respondents significantly influenced the farmers' decision to practice improved crop variety as a response to climate change adaptation. The study's conclusions showed that a number of factors limited farmers' attempts to adapt to climate change. The study recommends that decisions regarding adaptation plans should concentrate on reducing these barriers.
Keywords: 330; Adaptation; Binary logistic regression model; Climate change; Indigenous and Improved technologies; Smallholder farmers